The Strategic Role of Qiyas Theory on Elasticity of Islamic Law in Solving Contemporary Issues - Sanuri, Sanuri (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
This study highlights the role of qiyas in the elasticity of Islamic law in resolving contemporary issues of Muslims which do not have clear legal provisions in the nass, both in al-Qur'an and al-Sunnah. This is a qualitative research and the data collected through documentary in the form of texts directly related to qiyas theory. Furthermore, the data was analyzed using content analysis technique. To parse this theme, there are several important points, namely: (1) Al-Qur'an and al-Sunnah as revealed shari'ah; (2) Islamic law: between religious humanism and liberal humanism; (3) Qiyas in the lens of Ash'ariyyah and Mu'tazilah scholars; and (4) Qiyas and elasticity of Islamic law. The result of this study is that qiyas has enormous potential in proving and embodying the elastic character of Islamic law in providing answers to various contemporary problems of Muslims. However, the notes for qiyas, as offered by the madhhab scholars, currently need to continue to be developed, with an attitude of openness, to accept various scientific and technological developments that continue to experience very rapid leaps.